1994
DOI: 10.1073/pnas.91.23.11022
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus variants from Vietnam are classifiable into the seventh, eighth, and ninth major genetic groups.

Abstract: Thirty-four (41%) of 83 hepatitis C virus (HCV) isolates from commercial blood donors in Vietnam were not classifiable into genotype I/la, H/lb, HI/2a, IV/2b, or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 24 publications
4
141
1
Order By: Relevance
“…Genetic variants of HCV are known to be widely spread around the world. Genotypes 1, 2 and 3 are found on all continents, but in some geographical areas, such as Africa and Southeast Asia, viral isolates are highly divergent and particular genotypes or subtypes are predominant (13)(14)(15)(16). These data suggest the existence of a long-term endemic infection in these areas and some investigators have hypothesized that HCV might have originated in such places (17).…”
Section: Discussionmentioning
confidence: 87%
“…Genetic variants of HCV are known to be widely spread around the world. Genotypes 1, 2 and 3 are found on all continents, but in some geographical areas, such as Africa and Southeast Asia, viral isolates are highly divergent and particular genotypes or subtypes are predominant (13)(14)(15)(16). These data suggest the existence of a long-term endemic infection in these areas and some investigators have hypothesized that HCV might have originated in such places (17).…”
Section: Discussionmentioning
confidence: 87%
“…Other type-specific polymorphisms in this region occur in regions predicted to be unpaired (positions -331, -330, -329, -313, -308, -307, -305 and -284) or strengthen proposed stem structures (-271, -264 and -279). The direct repeats of CACUCC at positions -319 and -304 noted previously (Takamizawa et al, 1991) occur in all sequences including this region, and are also reported for sequences of type 6 and other novel types from Vietnam (Tokita et al, 1994a).…”
Section: Structural Implications Of 5"ncr Sequence Variationmentioning
confidence: 82%
“…Furthermore, the accuracy of the LiPA could be increased by designing primers to recognize types 3b, 5 and 6. Neither typing system would distinguish all virus subtypes, or some novel genotypes discovered in Vietnam with 5'NCR sequences similar to type 1 viruses (Tokita et al, 1994a), but from previous extensive surveys these virus types are probably of limited distribution (Bukh et al, 1993;Simmonds et al, 1993 a). Finally, the range of virus types and subtypes present in any one geographical region is generally limited Davidson et al, 1995), and so the task of distinguishing between virus types in any one country would therefore be simpler than for the world wide collection of sequences analysed here.…”
Section: Accuracy Of Methods Using 5'ncr Polymorphisms For Virus Genomentioning
confidence: 99%
See 1 more Smart Citation
“…The most common genotypes in Vietnam were genotypes 1 and 6, about 40% each, followed by genotypes 2 and 3, ranging from 5% to 17%. 11,[35][36][37][38][39][40] HIV and viral hepatitis coinfection. As a consequence of shared transmission route, coinfection of HIV and hepatitis B and C is common.…”
Section: Overview-hepatitis B and C And Hiv Coinfection In Vietnammentioning
confidence: 99%